2000
DOI: 10.1002/1521-186x(200009)21:6<439::aid-bem4>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high peak power microwaves on the retina of the Rhesus monkey

Abstract: We studied the retinal effects of 1.25 GHz high peak power microwaves in Rhesus monkeys. Preexposure fundus photographs, retinal angiograms, and electroretinograms (ERG) were obtained to screen for normal ocular structure and function and, after exposure, as endpoints of the study. Histopathology of the retina was an additional endpoint. Seventeen monkeys were randomly assigned to receive sham exposure or pulsed microwave exposures. Microwaves were delivered anteriorly to the face at 0, 4.3, 8.4, or 20.2 W/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Lu et al (2000) studied the retinal effects of 1.25 GHz high peak power microwaves in Rhesus monkeys, using fundus photographs, retinal angiograms and electroretinograms to evaluate ocular structure and function. The authors concluded that retinal injury is unlikely at 4 W/kg, and that functional changes at higher retinal SAR values are likely reversible.…”
Section: Ocular Effectssupporting
confidence: 90%
“…Lu et al (2000) studied the retinal effects of 1.25 GHz high peak power microwaves in Rhesus monkeys, using fundus photographs, retinal angiograms and electroretinograms to evaluate ocular structure and function. The authors concluded that retinal injury is unlikely at 4 W/kg, and that functional changes at higher retinal SAR values are likely reversible.…”
Section: Ocular Effectssupporting
confidence: 90%
“…Retinal degeneration in monkeys was also found by Kues and Monahan [] for SAR values in excess of 3.9 W/kg (2.45 GHz pulsed microwave) and 3.5 W/kg (1.25 GHz pulsed microwave). Lu et al [] showed that cone photoreceptor b‐wave from monkey electroretinogram (ERG) was SAR dependent and was enhanced by SAR values of 8.4 and 20.2 W/kg, but not by 4.3 W/kg. No degenerative change or ERG depression was seen in this study.…”
Section: Introductionmentioning
confidence: 71%
“…In other in vitro studies on neuronal responses, which found effects of RF‐EMF on neuronal function, it remains unclear how good the temperature was controlled during measurements [Hossmann and Hermann, ]. With respect to retinal effects, an in vivo study on rhesus monkey retina by Lu et al [] is in agreement with our results when considering SAR values below 8.4 W/kg. Scotopic b‐waves in the electroretinogram (ERG) were within normal range for SAR values up to 20.2 W/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no mechanism has been clearly exposed, some authors have identified deleterious effects in different parts of the eye, such as the lens [1113], the cornea [14, 15], or the retina [15]. Such results were frequently related to an oxidative stress increase [16].…”
Section: Introductionmentioning
confidence: 99%